2011
DOI: 10.1094/pdis-10-10-0721
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pepper mottle virus in Bell Pepper in Taiwan

Abstract: Bell pepper (Capsicum annuum L.) plants exhibiting systemic mild mosaic, vein yellowing, and leaf malformation were collected from Puli City in 2006. Double-antibody sandwich (DAS)-ELISA was used to test these samples for Chilli veinal mottle virus (ChiVMV) infection using polyclonal antibodies. In addition, Chenopodium quinoa, C. amaranticolor, and Nicotiana benthamiana plants were mechanically inoculated with sap extracted from collected samples. Ten days postinoculation, chlorotic local lesions were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The P0 of PoPeVYV has only 77.5–87.1% amino acid identity to the other PeVYVs, which could account for the distinct symptoms but the field plants were also infected with other viruses (PeVYVs, ChiVMV, ChiRSV, CMV etc.) as frequently happens in the field and which has also been reported in Taiwan and Thailand [ 20 , 21 ]. The severe viral symptoms in the field may therefore be a synergistic effect of mixed infection.…”
Section: Main Textsupporting
confidence: 53%
“…The P0 of PoPeVYV has only 77.5–87.1% amino acid identity to the other PeVYVs, which could account for the distinct symptoms but the field plants were also infected with other viruses (PeVYVs, ChiVMV, ChiRSV, CMV etc.) as frequently happens in the field and which has also been reported in Taiwan and Thailand [ 20 , 21 ]. The severe viral symptoms in the field may therefore be a synergistic effect of mixed infection.…”
Section: Main Textsupporting
confidence: 53%
“…The plants from the fields described here were infected with various viruses (PeVYVs, ChiVMV, ChiRSV, CMV, etc. ), and the severe viral symptoms of PeVYD in the field may therefore be a complicated synergistic effect of mixed infection (Cheng et al, 2011;Laprom et al, 2019;Zhao et al, 2021). The results of this study indicate that one factor affecting PeVYD symptoms is likely to be the co-infection of PoPeVYV and PoPeVYVaRNA.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have shown that the P0 proteins of poleroviruses display variable RNA silencing suppression activity, and induce distinct symptoms [18,19]. The P0 of PoPeVYV has only 77.5-87.1% amino acid identity to the other PeVYVs, which could account for the distinct symptoms but the eld plants were also infected with other viruses (PeVYVs, ChiVMV, ChiRSV, CMV etc) as frequently happens in the eld and which has also been reported in Taiwan and Thailand [20,21]. The severe viral symptoms in the eld may therefore be a synergistic effect of mixed infection.…”
Section: Main Textmentioning
confidence: 90%